2021
DOI: 10.3390/brainsci11020259
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, In Vitro Anticholinesterase, Antioxidant Activity and In Vivo Nootropic Effect of Ferula ammoniacum (Dorema ammoniacum) D. Don. in Scopolamine-Induced Memory Impairment in Mice

Abstract: Background: Ferula ammoniacum (D. Don) is one of the endemic medicinal plants that is traditionally used to treat a number of diseases. Although the plant has been used to enhance memory, the investigational evidence supporting the nootropic effect was unsubstantial. Hence, the rationale for this study was to assess the potential beneficial effect of F. ammoniacum seed extracts on learning and memory in mice. Methods: The powdered plant samples (aerial parts) were subjected to extraction ad fractionation. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Although the IC50 values for these molecules are significantly higher than donepezil, still having IC 50 values in this range suggests these molecules be a strong inhibitor of AChE activity. These findings are in line with previous findings where quercetin and rutin have been reported to possess the good potential to inhibit AChE activity in in-vitro 21, 22 , pre-clinical settings 23 , and clinical settings. 24 β-carotene, sumaflavone, and vitisinol-C also resulted in a dose-dependent inhibition of AChE activity, and their IC 50 values (508.60 ± 43.10, 694.18 ± 31.58, and 1009.87 ± 136.30 respectively) were observed to be higher than quercetin and rutin.…”
Section: Resultssupporting
confidence: 93%
“…Although the IC50 values for these molecules are significantly higher than donepezil, still having IC 50 values in this range suggests these molecules be a strong inhibitor of AChE activity. These findings are in line with previous findings where quercetin and rutin have been reported to possess the good potential to inhibit AChE activity in in-vitro 21, 22 , pre-clinical settings 23 , and clinical settings. 24 β-carotene, sumaflavone, and vitisinol-C also resulted in a dose-dependent inhibition of AChE activity, and their IC 50 values (508.60 ± 43.10, 694.18 ± 31.58, and 1009.87 ± 136.30 respectively) were observed to be higher than quercetin and rutin.…”
Section: Resultssupporting
confidence: 93%
“…Among them, chlorogenic acid, epigallocatechin gallate, quercetin, and ellagic acid have previously exhibited strong antioxidant and hepatoprotective activities ( Zhang et al, 2014 , Afifi et al, 2018 , Ashraf et al, 2018 , Aljelehawy et al, 2020 ). Plants have antioxidant properties depending on the content of phenol and flavonoids, due to which they may play a role in scavenging free radicals thus exhibiting protective effects in oxidative stress and related complications in animal models ( Nazir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, according to the guidelines of OECD, Met. Ext at dose 250 and 500 mg/kg body weight (maximum dose) that was 1/10th of 1500 and 5000 mg/kg dose were given to experimental animals in subsequent experiments to assess the hepatoprotective and nephroprotective effect of the extract ( Nazir et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…[1,7] Furthermore, it was demonstrated that asafetida possess hypotensive, antidiabetic, antitumor, chemopreventive, [1] antinociceptive, antiinflammatory, [8] anxiolytic [9] and antiepileptic effects in vivo, and antioxidant [10] and anticholinesterase activities in vitro. [11] Also, for various other isolates of Ferula species, the potential in treatment of some gastrointestinal (i. e., gastric ulcers), [12] neurological (i. e., epilepsy and neurodegenerative diseases) [13,14] and cardiovascular (i. e., hypertension) disorders, [15] and diabetes [16] was revealed in vivo, and spasmolytic, [17] anti-inflammatory, [18] antioxidant and antimicrobial activities, as well as cytotoxicity against some cancer cell lines were shown in vitro. [19] Chemical composition of different Ferula species was previously investigated.…”
Section: Introductionmentioning
confidence: 99%